Phenotypic diversity in maize landraces in Ghana - Obeng-Antwi, K.; Craufurd, Peter Q.; Menkir, A.; Ellis, R.H.; Sallah, P.Y.K. (2012)
Detailed knowledge of the genetic diversity among maize (Zea mays L.) germplasm is useful for their systematic and efficient use in breeding programmes. Two multivariate techniques were used to characterize 77 landraces collected from southern Ghana and four Ghanaian improved varieties. The objectives of the study were to (i) characterize Ghanaian landraces for agronomic and morphological traits, (ii) use agro-morphological traits to determine the variability of the local landraces and (iii) evaluate the landraces for adaptation to two major maize-growing zones in Ghana. Euclidean distance estimates from agro-morphological traits averaged 6.49 over all accessions and ranged from 2.30 to 13.61, indicating high phenotypic variability among them. Principal component analysis (PCA) showed that the first four principal components explained 69.8% of the total variability among the accessions. Grain yield, ear and cob diameters, and kernels per ear dominated the first PC; vegetative characters such as plant and ear heights, and days to anthesis and silking were the major discriminatory traits associated with PC2. Ear and kernel traits also appeared important in the third PC. The results will help in maintaining the landrace accessions and serve as a guide in designing breeding strategies that utilize Ghanaian maize genetic resources effectively.